The impact of exports and gross domestic product on Indonesian income per capita in the new normal era - Francisca Sestri Goestjahjanti (Universitas Sebelas Maret, 2021)
Our research has an important objective to analyze and discuss the influence of exports and GDP on Indonesia's per capita income in the new normal era. Hypothesis testing was carried out because of the use of explanatory research methods, emphasizing the relationship between exports, GDP, and income per capita. We use linear regression for processing and reviewing time-series data from 2008 to 2020. Our results suggest that there is a significant positive effect of exports on per capita income. We also find a positive and significant effect of GDP on per capita income and a positive relationship between exports and GDP on Indonesian per capita income.